1980
DOI: 10.1126/science.7403861
|View full text |Cite
|
Sign up to set email alerts
|

Sodium-Induced Elevation of Blood Pressure in the Anephric State

Abstract: Normotensive anephric rats infused with 2 milliliters of a hyperosmolar solution of either sodium chloride or mannitol showed an increase in arterial pressure that was very pronounced with the sodium chloride and that could be partly abolished by administration of an antagonist to the vasopressor action of antidiuretic hormone (ADH). Rats with congenital ADH deficiency subjected to the same treatment showed smaller increments in arterial pressure that remained unchanged after administration of the ADH antagoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
16
1
1

Year Published

1982
1982
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 13 publications
(6 reference statements)
3
16
1
1
Order By: Relevance
“…Subtotal nephrectomy per se was accompanied by a small tendency to elevated plasma AVP levels, as shown in figure 2, which is also in accordance with observations by other investigators 6 and probably reflects decreased elimination of AVP through the kidneys. 12 Maintenance on water ad libitum for 24 hours did not change AVP levels, whereas infusion of normal saline increased them by over fourfold.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Subtotal nephrectomy per se was accompanied by a small tendency to elevated plasma AVP levels, as shown in figure 2, which is also in accordance with observations by other investigators 6 and probably reflects decreased elimination of AVP through the kidneys. 12 Maintenance on water ad libitum for 24 hours did not change AVP levels, whereas infusion of normal saline increased them by over fourfold.…”
Section: Discussionsupporting
confidence: 91%
“…6 It also caused a decrease in HR, probably due to baroreceptor reflex activity. Maintenance on water ad libitum for 24 hours, without saline infusion, caused no blood pressure change from baselines in either subtotally-nephrectomized or intact animals.…”
Section: Discussionmentioning
confidence: 97%
“…3 ' ' 7 However, as in the present study, investigators found no immediate rise in pressure; rather, they observed an increase of blood pressure after 1 week but not earlier.…”
Section: Discussionsupporting
confidence: 50%
“…In 1980, Hatzinikolaou et al, 7 found higher blood pressures in normotensive anephric rats receiving acute infusions of hypertonic saline than in those receiving hypertonic mannitol. The pressor action of hypertonic saline was not completely inhibited by a vasopressin antagonist, and the difference between the blood pressure after vasopressin (AVP) blockade, and control was greater in the saline group.…”
mentioning
confidence: 99%
“…An increase in plasma osmolality induces several responses including an increase in sympathetic activity, blood pressure elevation, and the release of neurohormones, such as vasopressin and angiotensin II (Bealer 2000;Hatzinikolaou et al 1980Hatzinikolaou et al , 1981Stocker and Toney 2005;Weiss et al 1996). Part of these responses are mediated through activation of the hypothalamic paraventricular nucleus (PVN) driven by the circumventricular organs in which central osmoreceptors are located (Antunes-Rodrigues et al 2004;Stocker et al 2008).…”
mentioning
confidence: 99%